Using Panel Data on Income Satisfaction to Estimate the Equivalence Scale Elasticity - Johannes Schwarze (Institute for the Study of Labor (IZA), 2000)
In this paper a new method to estimate the equivalence scale elasticity using individual panel data on income satisfaction will be developed. In contrast to other subjective approaches, the present one benefits from the fact that no direct cardinal individual welfare function has to be specified. In addition, panel data enables different scale use by the respondents to be controlled. The approach gives straightforward evidence: Obviously there is an optimal elasticity at which people feel satisfied with their income.
Keywords: C23; D31; I31; 330; Equivalence scales; income satisfaction; panel data; Einkommensverteilung; Disparitätsmaß; Sozialpsychologie; Haushaltseinkommen; Elastizität; Panel; Schätzung; Deutschland